DIVERSIFIKASI PRODUK OLAHAN JAMUR TIRAM DI DESA BINONG PAMARAYAN - Muhammad Angga Anggriawan; Evi Dora Sembiring; Fika Alawiatul Billah; Sendy Risky (STAI Darul Qalam Tangerang, 2022)
Mangir Village is one of the villages located in Binong Village, Pamarayan District, Serang Regency. The Women Farmers Group (WFG) 'Bodas Berkah Abadi' is one of the farmer groups that specializes in developing oyster mushrooms (Pleorotus Ostreatus) in Kampung Mangir. This farmer group not only serves the sale of organic oyster mushrooms, but also sells mushroom seeds and baglog media to the public. A classic problem that is always felt by farmers when they find obstacles in selling products to the market which ultimately must end up in the hands of collectors. Of course this can cause the price to be lower than the market. Diversification of processed oyster mushroom products must be increased from just producing fresh organic oyster mushrooms to diversifying oyster mushroom processed products. Therefore, this service aims to provide knowledge transfer regarding the processing of oyster mushrooms in order to diversify products as value added so as to maximize the profits obtained. The method of activities carried out in community service includes counseling, demonstrations, exercises for making mushroom-filled cilok and cireng, discussions and questions and answers. The result achieved is that it is hoped that the housewives of Binong Village will feel inspired because they get new experiences in utilizing other biological sources as alternative food ingredients and as additional businesses in increasing family income